DEMAM SEBAGAI UAP NERAKA JAHANNAM: STUDI TAHLILI HADITS SHAHIH BUKHARI NOMOR 3264 - Naim Muhammad, MUHAMMAD NA'IMUL MUFLICH (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This study discusses and analyzes a hadith narrated by Imam Al-Bukhori in Sahih No. 3264 about fever as the Steam Of Hell then cool it with water, The purpose of this study was to determine the Hadith and understanding of Hadith content textually and contextually. Hadith fever that comes from the steam of hell is also understood contextually by using the method of understanding Hadith Al-Ṯuruq al Sunnah al-Nabawiyyah offered by Prof. Ali Mustafa Yaqub. This method is able to understand the Hadith fever derived from the steam of hell by considering majâz, takwil, illat, geography, Arab culture, social conditions and al-asbab al-w rūd Hadith (Hadith background). Researchers use the method of Library Research by using the book of turots, articles, journals, as a reference in writing. This study resulted in the conclusion : 1) Imam Al-Bukhori in the book of Sahih No. 3264 about fever as a vapor of Hell then cool with water and matannya sanad law is“Sahih“.2) understanding of the content of the hadith that in understanding this hadith is not enough to use textual understanding alone but with a contextual approach، kalimat Demam sebagai Uap Jahannam maka Dinginkanlah dengan Air, it is as hot as the heat of hell. this expression means majaz is tasybih, like the heat of a fever compared to the steam of Hell, its meaning is in the form of majazi.